Research on Pressure Relief Method of Close Floor Roadway in Coal Seam Based on Deformation and Failure Characteristics of Surrounding Rock in Deep Roadway - Jianjun Cao; Benqing Yuan; Siqian Li; Zunyu Xu; Qihan Ren; Zhonghua Wang (Geofluids)
To solve the high-stress hazard faced in the process of deep mining process, the pressure relief characteristics of gas bearing coal and the deformation characteristics of surrounding rock in deep roadway are studied by means of laboratory test, similar simulation analysis, and field investigation. The investigation results and engineering application showed that the specimens could more easily reach the failure point due to the axial pressure relief under high confining pressure. In addition, the deformation and failure degree of the surrounding rock was higher due to the disturbance from the deep high-stress roadway. The scope of the height affected by the pressure relief of the overlying strata reached above 10 m. Moreover, the initial gas emission could reach 4.41–14.39 times that of the original coal seam by drilling a hole in the coal seam at 10 m from the roof. Thus, the short-distance floor roadway exerted an obvious pressure relief effect on the overlying coal seam.